Two cesarean deliveries after hemi-hysterectomy due to gestational trophoblastic neoplasia - Kentaro Kai; Yasushi Kawano; Mitsutake Yano; Mamiko Okamoto; Eiichi Hori; Kaei Nasu; Hisashi Narahara (Elsevier, 2018)
Objective: Although uterine didelphys per se is not associated with an impaired ability to conceive, the association between uterine anomalies and gestational trophoblastic neoplasia (GTN) remains unclear. The management of chemotherapy-resistant GTN in women with uterine didelphys raises a new issue regarding whether to perform a hemi-hysterectomy. Case report: A 23-year-old, gravida 1, para 0 Japanese woman was referred with a failed intermittent cervical dilatation for hematometra. Four years previously, she developed a GTN Stage III, score 5. As two cycles of chemotherapy with methotrexate (MTX) and one cycle of EMA-CO (etoposide, MTX, actinomycin D, cyclophosphamide and vincristine) did not result in remission, we performed an abdominal hemi-hysterectomy. After a canalization procedure and cervicoplasty were performed, the patient conceived naturally and prematurely delivered by cesarean section twice. Conclusion: A hemi-hysterectomy should be considered for fertility preservation when GTN develops on either side of a didelphic uterus and adjuvant chemotherapy does not result in remission. Keywords: Adjuvant chemotherapy, Fertility preservation, Gestational trophoblastic disease, Hysterectomy, Anomalies